Building an Educational Philanthropy Ecosystem: BAZNAS' Contribution Model in Indonesia - Latifatul Aminah (Journal of Social Research, 2025)
This study analyzes BAZNAS' innovative model in building an educational philanthropic ecosystem in Indonesia through three integrated strategies: infrastructure facilitation (Madrasah Fit to Learn program), educational assistance (BAZNAS Scholar School and BAZNAS Santri Scholarship), and institutional collaboration (partnership between universities and religious institutions). With the framework of Carol Weiss's Theory of Change, this study shows the transformation of zakat from charitable distribution to an instrument of sustainable development. Qualitative analysis of the BAZNAS program reveals a systemic approach that combines physical infrastructure improvement, human resource capacity development, and institutional networks to create long-term educational impacts. The findings of the study confirm the transformative potential of zakat in overcoming educational gaps while maintaining Islamic philanthropic values.